A relação entre o desenvolvimento das abordagens críticas da EF e a precarização do trabalho docente na escola pública - Couto, Maíra Lara (2015)
The 1980s was an important period of political/ideological clashes in the country, the result of this moment and under the influence of Education area, critical approaches to Physical Education were formulated. In contrast to historical use of EF to reaffirm interests of the elite, the critical approaches question this subordination and provide a didactic and methodological proposition, based on the social sciences and systematized in critical-surpassing and critical-emancipatory approaches. However, over twenty years after these formulations, these approaches are not hegemonic practices in school PE. Considering the neglect of context with public education in the country, amid the situation of structural crisis (Mészáros, 2011) of capital that proposes neoliberal policies as out of the crisis, throwing the burden of this crisis in the relation capital x labor, we aim at this study: understanding the relationship that exists between the development of PE critical approaches and precariousness of teaching profession in public school. For this, we based on the method of Historical-Dialectical materialism. As a research tool we will use semi-structured interviews with Physical Education teachers from the State System Education of Rio Grande do Sul (8th CRE), and literature review of the documentary analysis of educational laws from the 90s, because it is the moment when neoliberal policies entered harder in Brazilian education. After analyzing the collected elements, we realized that the few teachers who have ownership of these approaches found hard difficulties to develop them. We conclude that the precariousness of teaching profession is an important element that limits the development of critical approaches in public school. In addition, we realize that the organizational structure of the public school, an institution managed by the State and which has as one of its objectives to disseminate bourgeois ideology also appears as an obstacle to develop counter-hegemonic practices in school. Considering the contradictory movement that moves the concrete reality, we understand, even though the public school has a clear role in the reproduction of sociability where we live, there are cracks in this structure that allow the development of counter-hegemonic pedagogical practices, even if limited. Faced with this reality, we believe that the struggle to develop the critical approaches in school must be combined with the more general movement of struggle in defense of public school and structural change in society. Important steps and tools for this we have on the autonomous and united movements, such as the Fight Block created from the June Days and, in education field, the National Conference of Education and its preparatory stages.